The Translational Benefits of Sheep as Large Animal Models of Human Neurological Disorders - Murray, Samantha J.; Mitchell, Nadia L. (Frontiers in Veterinary Science, 2022)
The past two decades have seen a considerable rise in the use of sheep to model human neurological disorders. While each animal model has its merits, sheep have many advantages over small animal models when it comes to studies on the brain. In particular, sheep have brains more comparable in size and structure to the human brain. They also have much longer life spans and are docile animals, making them useful for a wide range of in vivo studies. Sheep are amenable to regular blood and cerebrospinal fluid sampling which aids in biomarkers discovery and monitoring of treatment efficacy. Several neurological diseases have been found to occur naturally in sheep, however sheep can also be genetically engineered or experimentally manipulated to recapitulate disease or injury. Many of these types of sheep models are currently being used for pre-clinical therapeutic trials, particularly gene therapy, with studies from several models culminating in potential treatments moving into clinical trials. This review will provide an overview of the benefits of using sheep to model neurological conditions, and highlight naturally occurring, genetically engineered, and experimentally induced sheep models that have demonstrated translational validity.